丹戎布拉国立大学师范学院汉语专业2015届学生使用 介词“和”、“对”、“跟”的偏误分析 - Ivon yarso; Lily Thamrin; Suhardi Suhardi (Universitas Tanjungpura, 2019)
AbstractThe preposition word is one of the most important parts in the type of Mandarin words that are often used in everyday life. Like the prepositions “he”, “dui”, “gen”, the way to use these three words is very many types, expressing the meaning conveyed is not the same, have definite differences. For Mandarin students to master the prepositions “he”, “dui”,”gen” must have certain difficulties, often incorrectly used. To understand the causes of errors in the use of the preposition words “he”, “dui”, “gen” in Mandarin study program students at the Faculty of Teacher Training and Education in Tanjungpura University, the author used a test method to analyze the misuse of the preposition words “he”, “dui”, “gen”, find the location of the problem prepositions “he”, “dui”, “gen”. Through this study, the author conclude that the percentage of errors in the use of the words “he”, “dui”, “gen” in the students of 2015 at Tanjungoura University were 56.4%, 55.0%, 40.2%. The cause of this error is the influences of foreign languages learned. Based on these findings, the author provide advice on the learning of these three words. Keywords: Preposition word, ”he”, “dui” and “gen”, Analysis of error